Human memory a reader - Shanks, David R. (London Arnold, a member of the Hodder Headline Group, 1997)
This reader is a collection of articles focusing on human memory since the 1980s. The readings have been chosen to provide a broad and up-to-date reflection of the main issues currently occupying memory researchers, with an emphasis on theoretical problems.
Section one: Concepts and knowledge -- Section two: Short term memory -- Section three: Reliability of memory -- Section four: Neuropsychology of memory -- Section five: Encoding and retrieval -- Section six: Models of memory -- Section seven: Memory and consciousness -- Section eight: Individual differences.
Includes bibliographical references and index.
Keywords: Memory